2022
DOI: 10.3390/nu14153023
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dietary Interventions in Prevention and Treatment of Iron-Deficiency Anemia in Pregnant Women: A Systematic Review of Randomized Controlled Trials

Abstract: Pregnant women are among the population groups most vulnerable to the development of anemia, as the overall iron requirement during pregnancy is significantly higher than in non-pregnant women. The aim of the systematic review was to assess the effectiveness of dietary interventions in the prevention and treatment of iron-deficiency anemia in pregnant women based on randomized-controlled trials. The systematic review was based on the PRISMA guidelines and is registered in the PROSPERO database (CRD42021261235)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
1
8
0
5
Order By: Relevance
“…This may not be due to the best practices though, as the prevalence of maternal anemia is higher in Sub-Saharan Africa [3], [49]- [51], however, this fact may be supported by the more interventions used to control anemia in Africa. Data collected from multiple center studies showed a more predictive effect (16%) of maternal anemia intervention as compared to single center studies Similar findings exist from other similar reviews although not during the COVID-19 pandemic [30], [52], [53]. In this context, the single center studies signified a major heterogeneity as compared to multiple center studies.…”
Section: Discussionsupporting
confidence: 79%
“…This may not be due to the best practices though, as the prevalence of maternal anemia is higher in Sub-Saharan Africa [3], [49]- [51], however, this fact may be supported by the more interventions used to control anemia in Africa. Data collected from multiple center studies showed a more predictive effect (16%) of maternal anemia intervention as compared to single center studies Similar findings exist from other similar reviews although not during the COVID-19 pandemic [30], [52], [53]. In this context, the single center studies signified a major heterogeneity as compared to multiple center studies.…”
Section: Discussionsupporting
confidence: 79%
“…This is due to the increase in plasma volume during pregnancy, which leads to a physiological decrease in haemoglobin concentration. Iron supplementation is known to increase the red cell mass, thereby increasing the oxygen-carrying capacity of pregnant woman [ 16 ]. Moringa supplementation has also been shown to increase haemoglobin levels, as well as other haematological parameters such as haematocrit, MCH, MCHC, and MCV values [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some cultures, or traditions, there are prohibitions or taboos against consuming certain foods during pregnancy, which can result in iron deficiency and cause anemia. Examples of dietary restrictions such as a ban on eating red meat, eggs, or other types of food rich in iron can reduce the nutritional intake needed to prevent anemia in pregnant women (3,6,7). The study found that food restriction was associated with anemia incidence on pregnant women (p-value = 0.005) < 0.05).…”
Section: Determinants Of Food Restriction and The Incidence Of Anemia...mentioning
confidence: 93%
“…According to the World Health Organization (WHO), anemia is a major global health problem affecting nearly two billion people worldwide (2). The population groups most vulnerable to this condition are women of childbearing age and pregnant women (3). Given these serious health consequences, WHO has indicated that one of its Global Nutrition Targets is to reduce the frequency of anemia on women of childbearing age by 50% by 2025 (4).…”
Section: Introductionmentioning
confidence: 99%